2022
DOI: 10.3390/ijerph191711100
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Payment Scheme Changes on Medication Adherence and Persistence of Patients Diagnosed with Depression in Korea

Abstract: As of 1 July 2018, the Korean National Health Insurance Service (NHIS) changed the fee schedule for individual psychotherapy (IP). We sought to analyze the impact of the IP payment scheme changes on the medication adherence and persistence of patients diagnosed with depression in Korea. We utilized the NHIS claims database from 2017 to 2019. Patients who were newly diagnosed with depression and utilized IP and were prescribed antidepressants during the study period were included. Adherence was measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Of all the selected studies, the majority, 35 (89.7%), included one cohort, three studies (7.69%) included two cohorts ( Stang et al, 2007 ; Kales et al, 2013 ; Shin et al, 2022 ) and one study included three cohorts ( Liu et al, 2010 ). Multiple cohort studies were compared based on characteristics such as the dose or type of medication, ethnicity, and the healthcare insurance coverage (e.g., uninsured, partially or fully insured).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all the selected studies, the majority, 35 (89.7%), included one cohort, three studies (7.69%) included two cohorts ( Stang et al, 2007 ; Kales et al, 2013 ; Shin et al, 2022 ) and one study included three cohorts ( Liu et al, 2010 ). Multiple cohort studies were compared based on characteristics such as the dose or type of medication, ethnicity, and the healthcare insurance coverage (e.g., uninsured, partially or fully insured).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies ( McLaughlin et al, 2007 ; Stang et al, 2007 ; Yen et al, 2009 ; Yau et al, 2014 ) that evaluated age (continuous) as a predictor found that the treatment adherence rate was higher among older individuals. Among the studies comparing different age groups, one study indicated a higher likelihood of treatment adherence among individuals between the ages of 35–65 compared to younger individuals ( Shin et al, 2022 ). Three other studies also provided similar data, indicating that elderly patients have better adherence rates than patients under 60 years ( Sirey et al, 2001 ), 45 years ( Merrick et al, 2012 ) or 35 years ( Kogut et al, 2016 ) of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study underscored the need for ophthalmologists to particularly address younger male patients to enhance adherence. Concurrently, Shin et al 175 evaluated the influence of psychotherapy payment modifications on medication adherence in Korean patients with depression, leveraging the KNHICD. Their results highlighted superior medication adherence and persistence in women aged 19-34 compared to their counterparts aged 50-64.…”
Section: Explored Medication Adherence Among Korean Patientsmentioning
confidence: 99%
“…The incidence of depression, which has increased by 25% since the COVID‐19 pandemic, is often associated with physical illness, loss of occupational function, and low quality of life issues, and could also lead to high rates of suicide (Shin & Bae, 2023). Therefore, the discovery of the relationship between PCSK9 and depression can help the careful use of PCSK9 inhibitors in this population and prevent various problems that may occur.…”
Section: Effects Of Pcsk9 On the Cns Diseasesmentioning
confidence: 99%